Best practices in defence of competition in Argentina and Brazil : useful aspects for Central America - Petrecolla, Diego (CEPAL MexicoMX, 2007)
Focuses on recent legislation on defence of competition and its enforcement in Argentina and Brazil. Makes recommendations for the Central American countries whose legal frameworks are in the process of being drawn up or are under review, while others are just beginning to operate.